Study of Rooftop Hybrid Solar Wind Renewable Energy Applications for East Coast of Peninsular Malaysia - Liew, Zhi Bin (IRC, 2021)
The project is focused into improve the power generation of rooftop solar wind turbine by increasing the speed of prevailing wind flow through wind turbine.